KAJIAN PENDAHULUAN UJI TOKSISITAS EKSTRAK AIR MISELIA DAN TUBUH BUAH JAMUR SHIITAKE (Lentinus edodes) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BST) - Noor Erma NS; Tri Sundari; Arie Ika Susanty; Dwi Riani Oktavia Palupi; Isnaeni; Sukardiman (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
Shiitake mushroom (Lentinus edodes) is one of the wood mushroom types that can be consumed as a food as well as for a medical purpose. Lentinan, a polysaccharide contained in shiitake, is well known for its use on cancer medication. Mycelium of Shiitake mushroom contains lentinan the same as other part of the mushroom like fruity body. Toxicity of the lentinan in mycelium compare to the fruity body has been first conducted by using Brine Shrimp Lethality Test (BST). Using Potato Dextrose Broth media with the growth rate of 3.88% did mycelium multiplications. Probit analysis showed that the toxicity of the mushroom’s cap, stem, and mycelium of Shiitake mushrooms is LC50 = 648.76507 mg/ml LC50 = 489.39444 mg/ml, and LC50 = 481.16941 mg/ml respectively.